1995
DOI: 10.1128/jb.177.18.5284-5288.1995
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis and overexpression of the Zymomonas mobilis tgt gene encoding tRNA-guanine transglycosylase: purification and biochemical characterization of the enzyme

Abstract: . We showed that this gene is able to complement the tgt mutation in E. coli SJ1505, and we determined its complete sequence. Four start codons were possible for this gene, resulting in proteins of 386 to 399 amino acids (M r , 42,800 to 44,300) showing 60.4% sequence identity with Tgt from E. coli. The smallest of the four possible reading frames, which was still extended at its 5 end compared with the E. coli tgt gene, was overexpressed in E. coli. The gene product was purified to homogeneity and was biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Conserved amino acids are shown in white on a dark gray background. The numbering refers to the Z. mobilis TGT sequence beginning at the fourth possible start codon GTG (Val), denoted by an arrow, as described previously (14). The secondary structure of the Z. mobilis TGT is shown above the sequences (11), whereas the predicted secondary structure elements of the QTRTD1 proteins, generated using the Porter program (27), are presented below the sequences.…”
Section: Qtrtd1 Variants Are Distantly Related To the Eukaryotic And mentioning
confidence: 99%
See 1 more Smart Citation
“…Conserved amino acids are shown in white on a dark gray background. The numbering refers to the Z. mobilis TGT sequence beginning at the fourth possible start codon GTG (Val), denoted by an arrow, as described previously (14). The secondary structure of the Z. mobilis TGT is shown above the sequences (11), whereas the predicted secondary structure elements of the QTRTD1 proteins, generated using the Porter program (27), are presented below the sequences.…”
Section: Qtrtd1 Variants Are Distantly Related To the Eukaryotic And mentioning
confidence: 99%
“…Asp-102, which was originally ascribed the role of active site nucleophile, functions as a general acid/ base during catalysis (12,10). Although, the E. coli and Z. mobilis TGT enzymes are monomeric in solution (14), at high protein concentrations the E. coli enzyme can oligomerize (15), and structural data from the Z. mobilis TGT has shown the formation of a 2:1 complex with tRNA; a possible functional requirement for catalysis (10).…”
mentioning
confidence: 99%
“…A second gene identified from the sequence of 36C2 was queuine tRNA ribotransferase. This enzyme is involved in the biosynthesis of the hypermodified tRNA nucleoside queuosine (Q) (33). Lastly, clone 33F5 exhibited homology with a gene encoding an ABC associated with mannopine transport (29).…”
Section: Vol 69 2001 Identification Of Brucella Abortus Genes 7739mentioning
confidence: 99%
“…For example, the eukaryotic TGT is a heterodimer that is comprised of a putative 60-kDa regulatory subunit and a 35-kDa catalytic subunit [13,14] while the eubacterial TGT has been considered to be monomeric [15,16] although a recent crystal structure shows the Zymomonas mobilis TGT to be a homodimer [17]. Additionally, the TGT from archaea is considerably larger, containing ca.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%
“…It is unclear if the trimeric structure is realized in vivo; however, it has been reported that the highly homologous TGT from Z. mobilis (ca. 60% similarity) exists as a monomer in the absence of tRNA [16]. Recently, studies in our laboratory have demonstrated that the E. coli TGT proceeds via a ping-pong kinetic mechanism whereby tRNA is the first substrate to bind to the enzyme [24].…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%